The relationship between hypothyroidism and physical exercise: impact on exercise tolerance and health - Schok, Katarzyna; Jasek, Jakub; Wiejak, Katarzyna; Skoczylas, Kamila; Mikulska, Julia; Rokicki, Sebastian (Journal of Education, Health and Sport, 2023)
Background: Hypothyroidism is a common disorder among patients and it is well known that individuals with hypothyroidism often have lower tolerance for physical activity. However, regular exercise can have a positive impact on health and quality of life of these patients. Objective: The aim of this work is to review the relationship between hypothyroidism and physical activity, including the potential benefits of physical exercise for individuals with hypothyroidism, as well as the factors that may limit exercise tolerance in this population. Method: A literature review was conducted on databases such as PubMed and Google Scholar using terms „hypothyroidism”, „physical exercise”, „exercise tolerance”, „quality of life”, „thyroid function”. Results: People with hypothyroidism engage in sports less frequently, which may be due to the influence of hypothyroidism on the lungs, heart and muscles, which can cause impaired exercise tolerance. However, physical exercise in individuals with hypothyroidism may have a positive impact on thyroid function, depressive states and cognitive functions. Conclusions: Studies suggest that exercise can have positive effects on thyroid function, mood and symptoms of depression in patients with hypothyroidism. Therefore, incorporating regular physical activity into the management of hypothyroidism can be an important strategy for improving health outcomes in these patients.